The Skeletons in the Light of the Recent Archeological Discoveries of the Prehistoric Sites in Kurdistan Region (Anthropological Archaeologist Study). - Zainab Tahir Mohamad; Noman Jumaa Ibrahim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This research specifically covers the beginning of new archaeological excavations, and mostly deals with all such works carried out by foreign archaeological missions and in coordination with antiquities departments and academic and archaeological bodies in Iraqi Kurdistan. In fact, there have been research and excavations in previous centuries in order to identify human life, history and civilization as an attempt to learn many other cultural aspects including ancient architecture, pottery, stone tools, and most importantly, the discovery of human and animal skeletons in prehistoric sites in Iraqi Kurdistan, and all these discoveries are reliable and important material resources that contribute As the title of the study suggests, the discovery of bones collected from different sites in Iraqi Kurdistan that were analyzed in advanced laboratories to learn more about substances or elements buried with skeletons. This is known as anthropology.